2015
DOI: 10.14486/ijscs398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Description Of Fitness Level? Physiological And Anthropometric Profiles Of Selected Versus Non Selected Iranian National Team Table Tennis Players

Abstract: Objectives: The aims of this study were to comparison and describe the anthropometric characteristics physical fitness and physiological profile of the first 5 and the lower ranked elite male Iranian national table tennis players, who participated in table tennis championship, to compare the anthropometric data, physical fitness and physiological profile of the first 5elite tennis players on the ranking with the lower ranked players, and to establish an anthropometric and physiological profile chart for elite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Therefore, there is a need to increase the training measures that shape exibility in the motor training process of these young players. Table tennis belongs to the group of sport disciplines where the level of coordination and speed skills, especially of the upper limbs, should be at the highest level [53][54][55][56]. This study showed that the table tennis players obtained the best results in the SHR test assessing the level of these abilities.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, there is a need to increase the training measures that shape exibility in the motor training process of these young players. Table tennis belongs to the group of sport disciplines where the level of coordination and speed skills, especially of the upper limbs, should be at the highest level [53][54][55][56]. This study showed that the table tennis players obtained the best results in the SHR test assessing the level of these abilities.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, there is a need to increase the training measures that shape flexibility in the motor training process of these young players. Table tennis belongs to the group of sport disciplines for which the level of coordination and speed skills, especially of the upper limbs, should be at the highest level [ 53 , 54 , 55 , 56 ]. This study showed that the table tennis players obtained the best results in the SHR test, assessing the level of these abilities.…”
Section: Discussionmentioning
confidence: 99%
“…9,8 Daya tahan jantung paru yang baik sangat dibutuhkan oleh atlet cabang olahraga tenis meja karena tenis meja merupakan aktivitas predominan anaerobik yang membutuhkan tingkat pengkondisian aerobik yang tinggi untuk menghindari kelelahan dan membantu pemulihan. 11 Dari hasil penelitian didapatkan bahwa komponen kondisi fisik predominan atlet putra dan putri cabang olahraga tenis meja Jawa Barat PON XVIII/2012 Riau yaitu daya tahan jantung paru berdasarkan standar KONI pusat berada pada kategori cukup.…”
Section: Diskusiunclassified